A STUDY ON PAIR WORK AND STORYTELLING FOR TEACHING SPEAKING FLUENCY - Ayu Fitrianingsih (IKIP PGRI Bojonegoro, 2017)
Abstract: A Study on Pair Work and Storytelling for teaching Speaking Fluency. Fluency in speaking creates a growing demand of Indonesian people on starting teaching English at elementary school level. The aim of this study is to analyze the implementation of pair work and storytelling, and the impact of it toward students’ speaking fluency. This study employed a qualitative research design, in order to be able to observe and get detail information on how the students react and interact in the speaking class. This research was conducted on the fifth grade of primary school students. Necessary data were gathered using interview, observation, and the document analysis. The result of this study revealed that pair work and story telling were implemented in the elaboration step in which the students are assigned to do the worksheet. In the implementation process, the teacher inserted motivation to encourage the students. Besides, the implementation of pair work and story telling in the speaking class drives the students to have speech rate around 110 – 130 wpm, silent pauses in 1 – 3 seconds and some fillers.Keywords: Pair Work, Story Telling, Speaking FluencyAbstrak: Studi Pengggunaan Metode Pair Work dan Storytelling untuk Mengajar Kelancaran dalam Keterampilan Berbicara. Kelancaran berbicara menyebabkan semakin meningkatnya minat penduduk Indonesia untuk mulai mengajarkan bahasa Inggris pada tingkat sekolah dasar. Tujuan dari penelitian ini adalah untuk menganalisis penerapan pair work dan story telling, serta dampaknya terhadap kelancaran berbicara siswa. Penelitian ini menggunakan desain penelitian kualitatif, agar dapat mengamati dan mendapatkan informasi rinci tentang bagaimana siswa saling berinteraksi di kelas speaking. Objek penelitian merupakan siswa kelas lima sekolah dasar. Data yang dibutuhkan diperoleh dari hasil wawancara, observasi, dan analisis dokumen. Hasil penelitian mengungkap bahwa pair work dan story telling diterapkan pada tahap elaborasi dimana siswa ditugaskan untuk mengerjakan worksheet (lembar kerja). Dalam penerapannya, guru menyisipkan motivasi kepada para siswa. Di samping itu, penerapan pair work dan story telling di kelas speaking mampu mendorong siswa memiliki kecepatan berbicara sekitar 110 – 130 kpm, jeda dalam 1 – 3 detik dan beberapa idiolek.Kata kunci: Pair Work, Story Telling, Kelancaran Berbicara